Link Between Body Composition, Sprint and Vertical Jump in Young Elite Soccer Players from Chile [Relação Entre a Composição Corporal, Sprint E Salto Vertical Em Jogadores de Futebol Juvenil de Elite Do Chile] [Vínculo Entre Composición Corporal, Sprint y Salto Vertical en Futbolistas Jóvenes de Élite de Chile] - Aedo-Munoz, E (Universidad Nacional, 2021)
The objective was to know the relationships between indicators of body composition and physical performance in elite young players and to determine if there are differences between playing positions and series. The sample was of selected U-15 (n=24) and U-17 (n=20) male players, divided by playing position. Body composition, fat mass percentage (%MG) and muscle mass percentage (%MM) indicators were evaluated. Squat Jump (SJ), Countermovement Jump (CMJ), linear velocity in 10 (T10) and 30 meters (T30) were evaluated. Body composition and physical performance variables were related, and differences between playing positions and between categories were sought. Significant large associations were found in the U-15 category between %MM with SJ and CMJ, and moderate associations between %MG with T10, SJ and CMJ. In the U-17 category, a significant large association was found between %MM and T30, and between %MG and T30. Significant differences in %MG were found in the U-17 category between goalkeepers vs. defenders and forwards. Moderate significant differences were found in %MM between categories and very large differences in T10 and T30, and a moderate difference in SJ. It is possible to conclude that the body composition %MM and %MG is related to physical performance. In addition, there are differences in %MG between goalkeepers vs. outfield players and differences in body composition and physical performance variables between U-17 and U-15 players. The results obtained can be used as a reference or as parameters for comparison of young players at the national level in the detection of talent. © 2021 MHSalud. All rights reserved.